Factors Affecting the Implementation of Financial Accounting Standards for Micro, Small and Medium Entities in West Surabaya City - Abdillah, Hamzah Lini (PT FORMOSA CENDEKIA GLOBAL, 2024)
Indonesia's economy relies heavily on MSMEs or micro, small and medium enterprises. However, MSMEs still face many challenges, especially in terms of smooth financial reporting. The aim is to introduce small and medium enterprises (MSMEs) to the application of SAK EMKM. The study population was all MSME owners in West Surabaya City. The probability sampling technique was used to select 165 small and medium enterprises (MSMEs), or the largest number of respondents. Descriptive analysis and multiple regression were used to collect data. The results showed that the application of SAK EMKM in MSEs was influenced by various factors including information, owner motivation, HR competence, socialization, and educational background. It is recommended that MSMEs follow SAK EMKM in preparing their financial statements. Additional related parties that can help socialize SAK EMKM include the East Java Provincial Cooperative, the MSME Office, and the Indonesian Accountants Association (IAI).